Consolidation of glass fiber-polypropylene towpregs by compression moulding - Silva, J. F. (2006)
In this work a theoretical model describing the consolidation of glass fibre-polypropylene (GFfPP) towpregs into composites by compression moulding is studied. Such model relates the constant pressure applied by the press to the other processing operational (consolidation time and temperature) and material variables (fibre/polymer content and packing arrangement, matrix viscosity and powder and fibre dimensions). Compression tests were carried at different temperatures and constant press pressures on unidirectional GFfPP towpreg preforms. The experimentally determined displacement/time curves were compared to the model simulations assuming an isothermal consolidation and two different fibre/polymer packing arrangements, one triangular and the other hexagonal. The results obtained showed that the towpreg consolidation could be successfully predicted using the model under study.